Body and public policies for educational quality in Villavicencio: teacher training, infrastructure, and school dropout (Impetus, 2025)
The progress of the results of this study generates various reflections on the public policies implemented in Villavicencio that have attempted to enhance and improve the quality of education. In this case, we will focus on three key elements: teacher training, educational infrastructure, and school dropout. These topics are highly relevant in the field of education and student training. Similarly, this study adopts a qualitative approach, utilizing semi-structured interviews, which have allowed for a deep and contextualized understanding of the on-site educational situation. The sample consisted of 10 educational institutions selected for convenience. The results are highly reliable: in terms of infrastructure, there are deficiencies in public policies aimed at improving educational institutions concerning formative processes. Regarding school dropout, a lack of effective strategies from schools to retain students is evident. Although some initiatives foster student retention, social issues often outweigh students' decisions. Lastly, concerning continuous teacher training, although there are professional development programs, there is a lack of awareness about how to access them. Therefore, the discussion highlights the absence of effective dissemination strategies to enable teachers to acquire new knowledge in various school subjects.
Keywords: Schools; teachers; students; policies